The Relationship Between Mother's Knowledge Of Basic Immunization And The Completeness Of Toddler Basic Immunization In The Working Area Of Modoinding Community Health Center - Mamahit, Filia Sisilia; Mandagi, Chreisye K. F; Kolibu, Febi K (Asia Pacific Journal of Interdisciplinary Studies, 2025)
Complete basic immunization is important to provide so that the body can develop immunity and be protected from infectious diseases. Knowledge is a predisposing factor that influences the completeness of toddler immunization. This study aims to determine the relationship between maternal knowledge about basic immunization and the completeness of basic immunization in toddlers in the Working Area of Modoinding Health Center. The type of this research is quantitative analytic with a cross-sectional study approach. The research was conducted from December 2024 to February 2025. With a population of 173 mothers who have toddlers aged 12-24 months residing in the working area of the Modoinding Health Center. The sample consisted of 62 respondents using the Lemeshow formula. In this study, it was found that the majority of mothers had good knowledge with a percentage of 88.7% and those with sufficient knowledge 11.3%. The completeness of basic immunization among the majority of respondents had children with complete basic immunization status at a rate of 90.3% and incomplete at 9.7%. The research results with the chi-square test found a relationship between mothers' knowledge about basic immunization and the completeness of basic immunization for toddlers in the working area of the Modoinding health center (p = 0.001).